Daily Life Activities of Children during the Pandemic - Yersel, Beyhan Özge; Gunes, Lugen Ceren; Durualp, Ender (International Journal of Child Health and Nutrition, 2021)
The aim of this descriptive study was to examine the views of parents with children between the ages of 3-6 on their children’s daily life activities during the pandemic. The study sample was composed of 65 parents, among whom 60 were mothers, and five were fathers, who were selected with the snowball method and who had children between the ages of 3-6 and voluntarily participated in the study. The data were collected through the General Information Form and the Family Interview Form, which were developed in line with expert opinions. The collected data were analyzed using percentage and frequency values. The findings suggested that, during the pandemic, the children’s family relationships were positively affected; the duration of using technological tools increased; the children started to wash their hands more carefully; and duration of activities, such as drawing and chores, and plays increased. It was also found that the children mostly preferred piece assembly games; their physical movement needs were not fully satisfied; and there was no change in their health conditions, self-care skills, diet, sleep patterns, interactive book reading, and purposes of using technology. In line with the findings, parents, experts were given specific recommendations.